Predicting the impacts of human population growth on forest mammals in the highlands of southwestern Ethiopia. (April 2021) - Rodrigues, Patrícia; Dorresteijn, Ine; Guilherme, João L.; Hanspach, Jan; De Beenhouwer, Matthias; Hylander, Kristoffer; Bekele, Birhanu; Senbeta, Feyera; Fischer, Joern; Nimmo, Dale
Abstract: Projections of human population growth for 2050 indicate that Africa is expected to steadily increase its rural population, raising questions on how to best accommodate people while minimizing impacts on biodiversity. We explored the outcomes of scenarios of rural population growth mediated by housing development. We designed our scenarios based on (i) patterns of housing development (i.e., housing densification versus expansion), (ii) level of human population growth, and (iii) forest protection. Using camera traps, we surveyed mammals in the moist Afromontane forests of southwestern Ethiopia. We modelled mammals' responses to current and alternative housing development trajectories, using generalized additive mixed models. Our results suggest that (i) rural population growth is likely to negatively influence several mammal species, including a threatened predator (the leopard) as well as common crop raiding species such as baboons; (ii) negative impacts of population growth are likely to be exacerbated if new housing encroaches the forest (i.e., expansion), and likely to be less detrimental if houses are built within the existing human footprint (i.e., densification); and (iii) effects of human population growth can be modified by land-use decisions unrelated to biodiversity conservation, such as protection of economically important forest cover (native coffee forest in our study area). The location, extent and magnitude of housing development in southwestern Ethiopia can limit the ability of several mammal species to persist in the landscape. Our findings suggest that incorporating the ecological effects of housing development into landscape planning is fundamental to align conservation goals with development plans. Highlights: We surveyed mammals in undisturbed and managed coffee forests in Ethiopia. We modelled rural housing density projections to the year 2047. We predicted mammals responses to housing development scenarios. Development prioritizing built areas and forest protection had better outcomes. Landscape planning should combine development strategies and conservation.